The Determinants of Firms’ Characteristics on the Audit and Non-Audit Premium : An Analysis of Firms Listed in the Malaysia Stock Exchange - Joshi, Prem Lal; Krishnan, Anbalagan; Salleh, Nik Mohamad Zaki Nik (Indian Journal of Finance, 2017)
A number of studies have concentrated in exploring the audit service provided by audit firms, and the related fee charged. Factors such as an audit firm’s brand and its reputation and the skills and experience of auditors’ are some of the important variables influencing the audit service fee. There is a lack of evidence of a relationship between an audit premium and audit quality or the monopoly of an audit firm. In addition, a significant increase in the non-audit service fee has posed a dilemma to auditors’ ethical principles. It appears that the auditors have compromised their independence, objectiveness, and professionalism to provide the financial statement assurance in order to maximize their revenues. This impression has triggered the focus of this research to revisit the determinants that control the audit and non-audit fee and empirically explore whether the above claim is valid in the context of Malaysia’s business environment. This research is crucial due to increasing corporate scandals recently reported in Malaysia. The analysis was undertaken on the Annual Reports of 2012 using the partial least square (PLS) for a sample study of 100 firms listed in Malaysia’s stock exchange. The analysis revealed that only the firm characteristics of foreign shareholding, market capitalization, and foreign operations have a significant relationship with both the audit and non-audit fee.